2015
DOI: 10.1021/acs.jpcc.5b02920
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Covalent Functionalization on Thermal Transport across Graphene–Polymer Interfaces

Abstract: This Article is concerned with the interfacial thermal resistance for polymer composites reinforced by various covalently functionalized graphene. By using molecular dynamics simulations, the obtained results show that the covalent functionalization in graphene plays a significant role in reducing the graphene−paraffin interfacial thermal resistance. This reduction is dependent on the coverage and type of functional groups. Among the various functional groups, butyl is found to be the most effective one in red… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
117
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 144 publications
(127 citation statements)
references
References 53 publications
9
117
1
Order By: Relevance
“…[ [24][25][26] To study this effect, we randomly replaced 5% of the DNT-2's surface H atoms by -C 2 H 5 molecules. It is found that the total vdW energy change increased from ~ 10.5 eV to ~ 12.5 eV due to the presence of the -C 2 H 5 functional groups, which corresponds to about 20% increase in ISS (from ~ 58 MPa to ~ 68 MPa).…”
Section: Influential Factors On the Interfacial Shear Strengthmentioning
confidence: 99%
“…[ [24][25][26] To study this effect, we randomly replaced 5% of the DNT-2's surface H atoms by -C 2 H 5 molecules. It is found that the total vdW energy change increased from ~ 10.5 eV to ~ 12.5 eV due to the presence of the -C 2 H 5 functional groups, which corresponds to about 20% increase in ISS (from ~ 58 MPa to ~ 68 MPa).…”
Section: Influential Factors On the Interfacial Shear Strengthmentioning
confidence: 99%
“…2(a and b), were randomly distributed for the smallest length (50 Å) and then repeated to generate the desired simulation cells of FG. These two functional groups were considered because they are commonly observed in FG [11]. In addition, to graft the functional groups to the graphene surface, the hybridization was changed from sp 2 to sp 3 .…”
Section: Atomistic Model Of Graphene and Fgmentioning
confidence: 99%
“…The MD simulations were conducted using a large-scale atomic/molecular massively parallel simulator (LAMMPS) [18], and the interatomistic behaviors were described according to the polymer consistent force field (PCFF) potential [19]. Because the PCFF potential has been employed to model the mechanical properties of graphene and epoxy resin accurately [11,20,21], in this study, the PCFF potential was utilized to characterize the properties of graphene and graphene/epoxy nanocomposites. The functional form of the PCFF potential is expressed according to the summation of bonded and nonbonded energy.…”
Section: Atomistic Model Of Graphene and Fgmentioning
confidence: 99%
See 2 more Smart Citations